Multigenerational Families and Crisis Experiences: a Comparative Analysis of the Generational Novels by Ivana Šojat and Jagoda Marinić - JELEČ, Marijana; MANDIĆ, Marijana; Pavlović, Anita (Anafora, 2023)
This article is based on Škreb’s concept of literature as inseparable from the social and historical context. This anthropological basis is used for the analysis of the crisis phenomenon centred on the family system in the novels Unterstadt by Ivana Šojat and Restoran Dalmacija by Jagoda Marinić. In addition to the study of thematic, compositional, and genre features of the selected novels, the aim of the comparative analysis is to see the way in which literature contextualizes crisis in contemporary discourse. By using the theoretical determinants of previous research on crisis, family, and memory archiving, the article explores and compares the causes and indicators of family crisis, as well as reactions to it, thus contextualizing literature. This requires an analysis beyond the classical structuralist analysis and broadens the horizon of the literary work, therefore, the article will use the postclassical or new narratology, which is, in addition to the closed world of the novel, also oriented on the context. For this reason, the approach to analysis is to a certain extent interdisciplinary since the study of crisis, generation, and memory in literature requires a sociological, cultural, literary, and historical approach to obtain the overall understanding and interpretation of a novel in a wider context. Previous research on these novels has not focused on the experience of crisis within the framework of the family system, therefore this article provides new perspectives on the contextual character of the family crisis in contemporary literature, on the direct relation of the family to other social phenomena, and a new perspective in the research of the contemporary generational novel as a hybrid genre form.